Consumption- and productivity-adjusted dependency ratio with household structure heterogeneity - Xuehui Han; Yuan Cheng (Asian Development Bank (ADB), 2017)
In this study, we construct a new dependency ratio measure by taking into account the consumption needs of the young and elderly people, and the productivity of middle-aged people. Different from the way that Cutler et al. (1990) and Weil (1999) constructed the relative needs by using the average consumptions of each age cohort of people, we estimate the factor of relative needs of people at different ages based on a regression model, which embraces the household age compositions and size in the assessment. Our analysis uses household survey data from five developing countries in Asia - Bangladesh, Cambodia, the People's Republic of China (PRC), Thailand, and Viet Nam. To our best knowledge, this is among the pioneer work exploring such patterns for these countries. Focusing on the PRC, we further examine whether consumptions depend on the coresidence style. We found that (i) the consumption- and productivity-adjusted dependency ratio (both total and old dependency ratios) are consistently lower than the one that is traditionally defined across all five countries in our sample, and the differences vary from country to country; (ii) in the PRC, the differences between traditional dependency ratio and the consumption- and productivity-adjusted dependency ratio grow larger in more distant future; and (iii) in the PRC, the relatively younger elderly members between 65 and 72 years old help in reducing the consumption of young members in their households, and the elderly members who live alone consume more than their peers who live with their offspring. We also simulate the impacts of smaller households, urbanization, and economic growth on consumption for the PRC, based on our model.
Keywords: D10; E10; E21; H55; J11; 330; consumption- and productivity-adjusted dependency ratio; coresidence; householdstructure